The AfD's Election Campaigns on Euroscepticism: A Comparative Analysis of The 2019 And 2024 EP Elections (Third Sector Social Economic Review, 2025)
In the European Parliamentary Elections held in 2019, the Alternative for Germany Party  (AfD), which embraces European skepticism, succeeded in being the fourth party in terms of voting rate and became the second party to increase its vote rate the most after the Union 90/Green Party when compared to the previous European Parliamentary Elections (EPE). The AfD sharply criticized the EU administrative structure and advocated that radical changes should be made within the EU in the election campaign, in which European scepticism was felt intensely. In the study, it was aimed to reveal how the AfD reflected the EU administrative structure, what messages it gave against EU policies by examining the election campaign of the AfD on European scepticism in the 2019 and 2024 EPE. For this purpose, the election video prepared by the AfD for the election campaign was analyzed semiotically using the Organon Model of linguist Bühler. In the findings obtained, it was revealed that there was an attempt to form perceptions that the EU policies are to the detriment of Germany through video. In this way, it was concluded that the AfD tried to convince the German people that Germany should act more independently within the EU.
Keywords: Political Communication; AFD; Electoral Campaign; Euroscepticism; European Parliament